Argument-Driven Inquiry Model in Chemistry Learning: A Systematic Review - Siti Dzakiya Romadhoni; Sri Atun; Azlan Kamari (Jurnal Pendidikan Sains Indonesia, 2025)
Argument driven inquiry (ADI) model is an instructional learning model that combines argumentation with inquiry-based learning. The ADI model allows students to argue actively in the learning process. Previous research studies have found that the ADI model is widely applied in the field of chemistry. This study aims to systematically synthesize research acles related to the ADI model that focus on independent and dependent variables, chemical concepts, and conclusions in chemistry learning. This study uses the systematic literature review (SLR) method for 22 articles from the google scholar, ERIC (education resources information center) and scopus databases in the period 2016- 2025. Search through relevant keyword patterns, namely "ADI" and "chemistry education", index, title and abstract. The findings show that: 1) The dependent variables that are widely studied place the ADI model as a learning model, laboratory instructions, and levels in the inquiry method and the independent variables appear in the cognitive aspect, 2) The majority of study articles focus on the chemical concept of chemical equilibrium, 3) Most studies on the ADI model state that the ADI model is able to provide a positive influence or increase in learning competence in chemistry learning